The savvy musician : building a career, earning a living & making a difference - Cutler, David, 1971- (Pittsburgh, PA : Helius Press, 2010)
A guide for aspiring musicians who want to make their living doing what they love, covering such topics as building a brand, writing a business plan, creating a website, marketing, networking, the recording business, freelancing, finance, composing and arranging, and performance.
So you want to be a musician? -- The entrepreneurial mindset -- Minding your business -- Marketing is everything -- Print materials that scream success -- Pounding the virtual pavement -- The new recording paradigm -- Extraordinary people skills -- Personal finance for musicians -- Nice work if you can get it -- Funding your dreams -- Outstanding performance plus -- Artistry & relevance -- Leaving a legacy.
Includes bibliographical references (p. 323-330) and indexes.
Keywords: Music trade -- Vocational guidance; Music -- Economic aspects